ANALISIS BESARNYA NILAI TAKSIR BARANG, JUMLAH NASABAH DAN TINGKAT BUNGA TERHADAP PENYALURAN KREDIT PADA PT PEGADAIAN (Persero) UNIT PEMBANTU CABANG NATAR TAHUN 2010-2014 - R u d y - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
PT Pegadaian (Persero) is one alternative for people to get credit, both small scale andlarge scale, with easy and fast service. The more loans are given, means that the performance ofpawnshops is getting optimal. This is evidenced by the increase in lending by PT. Pegadaian(Persero) Natarsupporting branch unit.From the results of regression tests showed that the value of goods and the number ofcustomers has positive and significant impact on mortgage lending distribution.